Utilization of mixed adsorbents to extend frying oil life cycle in poultry processing - Udomkun, Patchimaporn; Innawong, B.; Siasakul, C.; Okafor, C. (Elsevier, 2018)
The effects were studied of two different adsorbent combinations (com I; bentonite: activated carbon: celite = 3:4:1 and com II; bentonite: activated clay: celite = 3:4:1 + 1% citric acid) on the physico-chemical changes of oil used continuously for deep-fat frying of chicken drumsticks. The results showed that the % FFA was reduced by 44.3, PV by 50.2, and FOS reading by 40.1% in com I whereas reductions of 41.6, 44.9, and 32.8%, respectively, were found in com II. The oil treated with com II exhibited a lighter color than with com I. The changes of oil color in com I were L∗ 30.7, a∗ 1.7, and b∗ 31.9%; in com II they were 53.2, 19.1, and 39.5% respectively. The higher the L∗ observed, the better the oil quality obtained because of the bleaching ability of adsorbents. Therefore, the use of such adsorbents is recommended for poultry processing.